Empowerment of cadres for parents in supervising children's use of gadgets in Puskesmas area in Surabaya, Indonesia - Indriatie, Indriatie; Novitasari, Aida; Mardiyana, Enung (Frontiers in Community Service and Empowerment, 2024)
The role of health workers provides health services to the community in improving the degree of public health. Its implementation can optimise Health Cadres (Surabaya City Health Office, 2019). The purpose of Community Service Activities is to increase the knowledge of cadres and parents who have elementary school children (Elementary School) about the role of parents in supervising the use of gawai in children Activity Participants; 3 lecturers, 6 students and 30 cadres of Surabaya Hebat, as well as 90 parents. The activity was carried out on 20 to 23 and 26 July 2023 in Pacar Kembang Village, Pacar Keling Surabaya Health Centre area. To achieve the objectives of the activity, lecturers carried out empowerment with the assistance of cadres, then the cadres provided assistance to parents. Implementation of assistance by providing material and modules on the role of parents in supervising the use of gawai in children. The results of cadre assistance before being given lectures and modules showed 76% less, 17% sufficient and 7% good. The results of parent mentoring activities showed 74% less, good and 13% sufficient. While the results after cadre assistance were good 40%, sufficient 37%, lacking 23%. It is expected that Surabaya Hebat cadres in Pacar Kembang Village will maintain the performance that has been achieved, and form working groups in their respective neighbourhoods to obtain health information in improving the level of health..